Identification of temporal pathomechanical factors during the Tennis serve - Martin, C.; Kulpa, R.; Ropars, M.; Delamarche, P.; Gribble, P. A. (Medicine & Science in Sports & Exercise, 2013)
Purpose: The purpose of this study was twofold: (a) to measure the effects of temporal parameters on both ball velocity and upper limb joint kinetics to identify pathomechanical factors during the tennis serve and (b) to validate these pathomechanical factors by comparing injured and noninjured players. Methods: The serves of expert tennis players were recorded with an optoelectronic motion capture system. These experts were then followed during two seasons to identify overuse injuries of the upper limb. Correlation coefficients assessed the relationships between temporal parameters, ball velocity, and peaks of upper limb joint kinetics to identify pathomechanical factors. Temporal parameters and ball velocity were compared between injured and noninjured groups. Results: Temporal pathomechanical factors were identified. The timings of peak angular velocities of pelvis longitudinal rotation, upper torso longitudinal rotation, trunk sagittal rotation, and trunk transverse rotation and the duration between instants of shoulder horizontal adduction and external rotation were significantly related to upper limb joint kinetics and ball velocity. Injured players demonstrated later timings of trunk rotations, improper differences in time between instants of shoulder horizontal adduction and external rotation, lower ball velocities, and higher joint kinetics. Conclusions: The findings of this study imply that improper temporal mechanics during the tennis serve can decrease ball velocity, increase upper limb joint kinetics, and thus possibly increase overuse injuries of the upper limb.